Fabrication, characterisation and modelling of fast flexible semiconductor nanomembrane electronics. (17th March 2014) - Qin, Guoxuan; Tu, Guoping; Cai, Tianhao; Ma, Jianguo; Ma, Zhenqiang
The novel properties of micro- and nanomembranes (e.g., flexible, stretchable, transferable, lightweight, capability of covering large area) offer great opportunities for a variety of new applications in electronics, photonics, microelectromehanical systems (MEMS), and other areas. This paper reviews the material fabrication and representative transfer techniques of nanomembranes for versatile functionalities. Characterisation and modelling of fast flexible nanoelectronics are reviewed: from individual devices such as thin-film transistors, diodes to circuits such as RF switches. This paper provides an overview of the fast flexible nanoelectronics based on transferable nanomembranes and indicates possible directions of semiconductor nanomembranes for exciting new science and nanotechnology.